Dilema Pengelolaan Sampah di Kota Makassar: Antara Kebijakan dan Realitas - Sukmawati, Sukmawati; Fatmawati, Fatmawati; Mustari , Nuryanti (Jurnal Ilmiah Administrasi Publik, 2025)
The gap between policy and reality in waste management in Makassar City is the main obstacle in achieving effective waste management goals. This research aims to analyze gaps in the implementation of waste management policies in Makassar City, with a focus on the differences between government motivation as outlined in laws or regulations and the reality of implementation in the field. A qualitative approach with a case study method was used to collect data through interviews, observation and documentation. The research results show that the performance of implementers in waste management in Makassar City is still far from the targets set in Government Regulation number 4 of 2011. The Environmental Service as a regulator is still lacking in implementing policies and supervision. Lack of public awareness, 3R-based waste management (Reduce, Reuse, Recycle) has not been implemented. The research found that there is a significant gap between policy and reality in waste management in Makassar City. The reasons include a lack of government commitment and capacity, low public awareness, and a less than optimal waste management system.